The risk profile of wheat rotation systems in the Middle Swartland under Conservation Agriculture: A SDRF and SERF approach winter cereals crop rotation risk - Nel, David Mathys Christoffel (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScAgric)--Stellenbosch University, 2022.